Pengaruh Model Learning Cycle 5E terhadap Kemampuan Pemahaman Konsep Matematis Peserta Didik Kelas VII SMPN 25 Padang - LEDITA MAYSARA (Jurnal Edukasi dan Penelitian Matematika, 2019)
The ability of understanding mathematically concepts is one of the learning objectives that are expected to develop optimally on self-learners. The purpose of this study was to determine whether the ability of understanding mathematically concepts learners whose learning model learning cycle 5E better than the ability of understanding mathematically concepts learners whose learning using conventional learning in grade VII of SMPN 25 Padang. The research is a quasi experimental research design with Static Group Design. Based on the data analysis of the final test results showed that the significant level of 0.05 by t-test is obtained P-value = 0.044, because P-value < a then Ho is rejected. It shows that the ability of understanding mathematically concepts learners use models learning cycle 5E better than the ability of understanding mathematically concepts learners with conventional learning in grade VII of SMPN 25 Padang. It shows that the application of the model learning cycle 5E influential to the ability of learners understanding of mathematically concepts. Keywords – Learning Cycle 5E Model, the Understand Mathematical Concept ability, Learning Model Conventional